Hubungan agama dengan Pancasila dalam perspektif konstitusi - Nahuddin, Yusuf Eko; Prastyo, Angga (Jurnal Cakrawala Hukum, 2020)
This study is a normative legal research and uses a statute approach and applies a descriptive analysis method which is conducted to analyze the relationship between Religion and Pancasila in the perspective of the 1945 Constitution., and their position in the 1945 Constitution. Religion becomes an object of study that is so complex in its relation to the state. The last time it was seen as the statement of YudianWahyudi (Chairperson of BPIP) about religion as an enemy of Pancasila. The 1945 Constitution which is positioned highest in the hierarchy of statutory regulations is an appropriate indicator in examining the relationship between religion and Pancasila, especially in the framework of a normative legal paradigm in Indonesia. In the main analysis of the results and discussion of this study, it was concluded that Religion is a supporter of the existence of Pancasila, and Religion cannot be contested or compared with Pancasila in the context of its position and position in the state and the administration of government. These results are so important for efforts to realize the objectives of the state, in order to underpin the administration of state in an effective and efficient state, without revisiting the problems and debates that have actually been resolved.How to cite item: Nahuddin, Y., Prastyo, A.(2020). Hubungan agama dengan Pancasila dalam perspektif konstitusi. Jurnal Cakrawala Hukum, 11(3). 282-290.doi:10.26905/idjch.v11i3.4070.Â